Arabic Language Education in Indonesian Schools Abroad: Balancing Identity, Adaptation, and Innovation - Ahmadi Ahmadi (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This study examines the dynamics of Arabic language education at Sekolah Indonesia Kuala Lumpur (SIKL), a representative of Indonesian Schools Abroad (ISA). It focuses on how the school maintains students’ linguistic and religious identity while adapting to the Malaysian socio-cultural context. Using a qualitative case study approach, data were collected through interviews with Arabic teachers, classroom observations, and document analysis. Findings indicate that SIKL strategically combines identity-based content, cultural adaptation, and pedagogical innovation. Teachers integrate Islamic values with local context through bilingual instruction, interactive methods, and digital tools. The study contributes to understanding how Arabic education in ISA can evolve to meet transnational educational demands while preserving core values.